2023
DOI: 10.1002/app.54787
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pickering emulsions stabilized with nano‐cellulose and nano‐chitin treated with deep eutectic solvent

Xinyu Wu,
Hailan Lian,
Yang Yuan
et al.

Abstract: Developing bio‐friendly and degradable Pickering emulsifiers as surfactants to replace traditional surfactants with bio‐toxicity is imperative in the food, coating, cosmetics, and pharmaceutical industries. Nanocellulose and chitin can be used directly as an emulsifier to prepare Pickering o/w emulsions. As the concentration of nanoparticles increases, the stability of the emulsion also increases, and an overly large nanoparticle aspect ratio is not conducive to the stabilization of the emulsion. In comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
0
0
Order By: Relevance
“…This suggested that the presence of NFC enabled higher stability of the emulsion due to its increased viscosity (slowed down Brownian motion) and higher zeta potential compared to the control. This finding was aligned with studies by Li et al (2020), Wu et al (2023), andFitri et al (2022).…”
Section: Creaming Stability At Accelerated Temperaturesupporting
confidence: 89%
“…This suggested that the presence of NFC enabled higher stability of the emulsion due to its increased viscosity (slowed down Brownian motion) and higher zeta potential compared to the control. This finding was aligned with studies by Li et al (2020), Wu et al (2023), andFitri et al (2022).…”
Section: Creaming Stability At Accelerated Temperaturesupporting
confidence: 89%